Kriminalisasi Jarimah Liwath Melalui Qanun Jinayah Sebagai Upaya Mengendalikan Kebebasan Amoral Manusia - Syarifah Rahmatilah (2022)
This study discusses the limitations of the freedom of will of every community, because everyone's freedom must be limited when dealing with the interests of state security, public order, the human rights of others with a balance of morals and religious values. The arrest of the perpetrators of jarimah liwath in Aceh indicates that these homosexuals still exist even though the Qanun Jinayah has been enacted. Prior to the enactment of this qanun, these people were supported by the Violet Gray institution which tried to promote the rights of homosexuals in Aceh, but in the end they were expelled from Aceh. The problem discussed is how to regulate the Qanun Jinayah regarding Homosexuals in terms of the aspect of moral freedom of the Acehnese people. This research is a literature study using a normative approach which is then explained descriptively. The results of this study explain that the regulation of the Qanun Jinayah against the criminalization of homosexual acts when viewed from the aspect of the moral freedom of the Acehnese people is very appropriate. This can be seen from the formulation of jarimah liwath in Qanun Jinayah with the aim of providing protection to morals. Morality and morality are very close. The people of Aceh are born into a Muslim majority. And Islam strongly rejects the immoral behavior of homosexuals, which is very dangerous for damage and not maintaining the dignity of humans and their descendants.